2021
DOI: 10.1024/0939-5911/a000706
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivität und assoziierte Konstrukte bei drogenabhängigen Patienten

Abstract: Zusammenfassung. Zielsetzung: Die vorliegende Pilotstudie untersuchte, ob selbstberichtete Achtsamkeit bei drogenabhängigen Patienten negativ mit impulsivem Verhalten assoziiert ist und ob dieser Zusammenhang über eine effektivere Emotionsregulation vermittelt wird. Ferner wurde die Relevanz der Differenzierung verschiedener Impulsivitäts-Facetten im Zusammenhang mit Craving und Abstinenzzuversicht untersucht. Methodik: Einunddreißig männliche drogenabhängige Patienten in stationärer Entwöhnung beantworteten F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…In contrast to previous studies (Roozen et al , 2011; Tziortzis et al , 2011; Reichl et al , 2021; Mahoney et al , 2015), we found no relation of general impulsivity to craving. However, incarcerated samples were not included in these studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies (Roozen et al , 2011; Tziortzis et al , 2011; Reichl et al , 2021; Mahoney et al , 2015), we found no relation of general impulsivity to craving. However, incarcerated samples were not included in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, given that emotional dysregulation seems to be related to impulsive behavior (Reichl et al , 2021), the concept of urgency (reacting impulsively to intense emotions) might be a potential mediator that should be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation